(3TQM GdcGJj Ydi EjSGZhLjs - (3GdcGJj, MSGe GdOjf MSf, J (B760 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGLH hLhOg aEf cJGH GdTjN CKjQ GdOjf GdCHgQj GdeTghQ HEjSGZhLj deG cGf Ydi HYV GdENhGf eJYSQG hYdi HYVge eJjSQG CQOJ Cf GcJH HGdJeGSge ChQGbG dJRjd JYSQgs
(3BNQgG (B:s
(3hGdNWGHI bjGS eDda ef ebOeGJ ebHhdI ef TNU eYJbO ajg Ch ef ebOeGJ eXfhfI ajg hGdZQV efg JQZjH GdfGS ajeG jfaYge ef CehQ eYGTge heYGOge ceG jaYdg GdNWHGA hGdhYGX hGdTYQ bjGS eDda ef ebOeGJ JfHSW efgG GdfaS Ch JfbHV hGdeZGdWI bjGS eDda ef ebOeGJ THjgI HGdMbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/579s
(3cTa GdXfhf (B1\206s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs